The Moral Impact of Synthesising Living Organisms: Biocentric Views on Synthetic Biology. (1st February 2012) - Deplazes-Zemp, Anna
This essay examines how biocentric positions assess the aims and planned products of synthetic biology. In this emerging field, scientists and engineers aim at designing and producing new life forms by various procedures. In this paper I explore whether, for biocentrists, 1) synthetic organisms have moral standing and, 2) the process of synthesising living organisms has moral implications. Because naturalness plays a role in some biocentric theories, synthetic biology - at first sight - seems to challenge the idea that all living organisms have moral standing. However, according to the interpretations that I offer, the biocentric positions discussed here would also assign moral standing to synthetic organisms. That living organisms have moral standing does not necessarily imply that it is morally problematic to synthesise them. However, different lines of biocentric argumentation suggest that in designing and synthesising living organisms, the moral standing of the product needs to be taken into account. This means among other things, that according to biocentrists, such procedures may lead to special responsibilities or require certain attitudes from scientists towards their products.